TiC MXene High Energy Density Cathode for Lithium–Air Battery. Issue 9 (15th July 2018) - Wang, Zhenyu; Chen, Xin; Shen, Fei; Hang, Xiaogang; Niu, Chunming
Abstract: MXenes are reported to be great supercapacitor and lithium‐ion battery material recently. In this article, the density functional theory (DFT) calculations show that using TiC MXene Ti n C n − 1 O2 ( n  = 2, 3, 4) as the cathode of lithium–air batteries (LABs) can potentially improve its efficiency by increasing the cathode conductivity and lowering the charging overpotential. In addition, the conservative predicted storage density is as high as ≈0.5 kWh kg −1 . Compared with the bulk TiC{111}, the favorable structural agreement between the TiC MXenes and Li2 O2, and better interfacial conduction help Li2 O2 continuously grow on the TiC MXene; and the higher specific surface area (SSA) makes more Li2 O2 deposition possible. The predicted reaction path calculations reveal that TiC MXenes have the charging overpotential of 0.13 V because they are excellent catalysts in the oxygen evolution reaction (OER). Thus, the lower charging overpotential can extremely suppress the side reactions and accelerate the OER rate. All the evidence supports that TiC MXene is a potential high energy density cathode for LABs. Abstract : Low cost, good conductivity, favorable structural agreement with Li2 O2, high specific surface area, and low charging overpotential (0.13 V) enable the TiC MXene to become a desirable cathode for lithium–air batteries (LABs). MXenes are successfully used in supercapacitors and lithium‐ion batteries. The further exploration of the TiC MXene and other MXenes will see potential applications in LAB development.